Diseases of sugarcane : major diseases - Ricaud, C. (Elsevier, 1989)
An extensive volume of Sugarcane Diseases and their World Distribution (Vol. I) was published by Elsevier under the auspices of the International Society of Sugar Cane Technologists in 1961. The present volume was intended to be a new edition of the book, but so many changes were required that a new book was needed. Only three chapters have been kept with slight amendments. The other chapters have been completely re-written. In fact with changes in importance of major diseases, four diseases previously treated have been left out; on the other hand, three new topics have been included in the new book, two new diseases and a chapter on sugarcane quarantine. The first chapter gives a brief account of the anatomy, morphology and physiology of the sugarcane plant to facilitate terminology and especially for a better appreciation of the effect of disease on the growth of the crop. Diseases are extensively treated as in Volume I, with a very good description of their symptoms and variation under different conditions and severity, all well illustrated by black and white figures and in a set of colour plates at the end of the book which will prove of valuable help for identification. The causal agents of the diseases are described giving synonyms, cultural characteristics, isolation methods and present knowledge on race variation, an aspect on which there has been quite an advance in knowledge since Volume I was published. New techniques of diagnosis are also given. Advances in research on the diseases over the last 25 years are well covered and supported by an extensive bibliography at the end of each chapter. The book has been edited by people having first hand experience in the field and in research on these diseases. Authors have been selected from among the most knowledgeable all over the sugar cane world, especially with due regard to the importance of the different diseases in their countries. The book should prove of immense value to those concerned with practical aspects of plant disease control in the field: pathologists, agronomists and crop specialists, including consultants, to those concerned with quarantine of the crop, for university lectures and students, and research scientists. In a pre-publication review D.J. Heinz and S.A. Ferreira of the Hawaiian Sugar Planters' Association stated: ``Much has changed and new information generated since the original version of this book was published in 1961. This new edition incorporates most of it, providing both the laboratory and field sugarcane pathologist a complete and authoritative guide to the major sugarcane diseases of the world. It is the best single book available on sugarcane diseases.''.